BIOGRAPHY. ARTICLE DEDICATED TO PROFESSOR EMIL CORDOŞ PHD - FRENŢIU, Tiberiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Professor Cordoș is part of a student generation that makes the most representative connection between the group of professors that founded the chemistry department in early 1920 and the generation that graduates in early 1960 and developed the chemistry department in both fundamental and engineering chemistry. This generation was the last to have the chance of lectures of great chemists of this country like Raluca Ripan in Inorganic Chemistry, Ioan Cadariu in Physical Chemistry or Ioan Tanasescu in Organic Chemistry.